Study of Financial Crisis Management in Tourism Industry - Alizadeh, Fereshteh; Manna, Mohsen; Kashisaz, Sara; Asadollahi Kheirabadi, Maryam; Basiri, Zeinab; Esmaeilimotlagh, Maryam (Opción, 2019)
The present paper aims to defining and analyzing crisis in the tourism industry. This paper proposed practical solutions to confront the crisis in tourism industry and used the Failure Mode and Effects Analysis technique via explanatory combinatorial methods. As a result, in order to manage the crisis, the structure of failure should be defined and codified for all processes of tourism system in the first stage. In conclusion, this industry is in need of prediction and systematic planning for probable dangers to maintain the continuation of activity and growth of profitability